Preparation and Performance Study of Drug-Loaded Film Materials Enhanced by Modified Cellulose Nanocrystals and Keratin - Sulaeva, Luisa; Füssl , Markus; Zhang, Johanna (Journal of Green Energy and Environmental Engineering, 2025)
Aldehyde-functionalized cellulose nanocrystals (DCNC) were prepared using the sodium periodate oxidation method. The aldehyde groups on DCNC can react with amino groups on keratin molecular chains, providing both crosslinking and enhancing effects on keratin film materials. Enhanced keratin drug-loaded film materials were prepared, and their drug release performance was studied. Research showed that modified cellulose nanocrystals provide crosslinking and enhancing effects. Compared to pure keratin film, the mechanical properties and water resistance stability of the DCNC/keratin composite film were significantly improved. The enhancement and crosslinking by DCNC effectively addressed the burst release phenomenon of pure keratin drug carrier films. The DCNC/keratin composite drug carrier film exhibited sustained release of the encapsulated drug. The research results not only contribute to the application of keratin natural polymer film materials but also provide a good reference for preparing other composite materials.